Frequency of KRAS and BRAF mutations in colorectal carcinoma and their association with clinical-pathological characteristics in a tertiary hospital in Kenya - Gakinya, Samuel; Njau, Allan; Abdallah, Abdulkarim; Nzioka, Ancent; Ogutu, James (Frontiers in Medicine, 2024)
Introduction Colorectal carcinoma is a leading cause of cancer morbidity and mortality globally. Its management includes the use of targeted therapy which require assessment for biomarkers to choose eligible patients. KRAS and BRAF mutations are biomarkers predictive of response to anti-EGFR therapy. This study aimed at determining the frequency of BRAF V600E and KRAS exon 2,3,4 mutations in colorectal carcinoma patients at the Aga Khan University Hospital Nairobi, Kenya. Methods Study participants were patients who had colectomy for colorectal carcinoma. They were identified from the laboratory information system. The patients age, gender and tumor location were determined from the medical records. The histological diagnosis, pathological tumor and nodal stage were confirmed by examining hematoxylin and eosin-stained slides prepared from the colectomy specimen. DNA was extracted from the specimens using Qiagen QIAamp DNA FFPE Tissue Kit and PCR performed using EntroGen KRAS/BRAF mutation analysis kit following manufacturer’s protocol. Results One hundred fourteen patients were enrolled. Colorectal carcinoma was significantly more common in males than females. The mean age at diagnosis was 58 years. Majority of the tumors were in the right colon, were of pathological tumor stage T3 and had nodal involvement. Forty six percent (46%) of the cases had KRAS mutations while 5.3% had BRAF V600E mutation. KRAS mutation was associated with a high pathological tumor stage and nodal involvement. Conclusion Colorectal carcinoma in our patients is more common in males and tend to occur at a younger age. The patients tend to have a high tumor pathological stage and nodal involvement at diagnosis. The high frequency of KRAS exon 2,3,4 mutation and low frequency of BRAF V600E mutations is similar to what has been reported in literature.